2012
DOI: 10.1016/j.neuron.2011.11.029
|View full text |Cite
|
Sign up to set email alerts
|

The Nogo Receptor Family Restricts Synapse Number in the Developing Hippocampus

Abstract: SUMMARY Neuronal development is characterized by a period of exuberant synaptic growth that is well studied. However, the mechanisms that restrict this process are less clear. Here we demonstrate that glycosyl-phosphatidylinositol-anchored cell-surface receptors of the Nogo Receptor family (NgR1, NgR2, and NgR3) restrict excitatory synapse formation. Loss of any one of the NgRs results in an increase in synapse number in vitro, whereas loss of all three is necessary for abnormally elevated synaptogenesis in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
170
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(184 citation statements)
references
References 33 publications
13
170
1
Order By: Relevance
“…Our morphological analysis showed that Nogo-A has a negative influence on the size of the PC bodies as well as the thickness, length, and complexity of PC dendrites. These results are well in line with previous studies in adult animals showing that Nogo-A is a negative regulator of the neuronal growth program (3,29), as well as with the recent findings showing negative regulation of dendritic length and complexity by Nogo-A and NgR1 in hippocampal neurons (7,30). PC dendrites are tightly packed and intermingled in the developing ML, and they were suggested to express NgR1 (31,32).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our morphological analysis showed that Nogo-A has a negative influence on the size of the PC bodies as well as the thickness, length, and complexity of PC dendrites. These results are well in line with previous studies in adult animals showing that Nogo-A is a negative regulator of the neuronal growth program (3,29), as well as with the recent findings showing negative regulation of dendritic length and complexity by Nogo-A and NgR1 in hippocampal neurons (7,30). PC dendrites are tightly packed and intermingled in the developing ML, and they were suggested to express NgR1 (31,32).…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, by binding to NgR1 or another yet unidentified receptor, Nogo-A activates the small GTPase RhoA (33), which has been shown to slow dendritic branch formation, yielding smaller and fewer branched dendritic arbors in various types of neurons (34). Notably, activation of RhoA has been recently identified as a mechanism by which NgR1 restricts dendritic growth and synapse formation in hippocampal neurons (30). Additionally, several studies have demonstrated that synaptic activity affects the dendritic arbor development (35,36), thus opening the possibility that by negatively regulating synaptic transmission at PF-PC synapses, Nogo-A in turn negatively regulates dendritic growth.…”
Section: Discussionmentioning
confidence: 99%
“…Several proteins have been shown previously to decrease the density of mammalian synapses, including Ephexin 5 (RhoA guanine nucleotide exchange factor) and Nogo receptors (41,42). In addition, regulator of synaptogenesis-1 (RSY-1) has been shown to regulate SYD-2/liprin-α-mediated presynaptic assembly negatively in Caenorhabditis elegans (43).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 In the adult CNS, the expression of neuronal Nogo-A remains elevated mainly in plastic regions such as in the hippocampus, olfactory bulb or neocortex, and in the dorsal root ganglia. 12 Nogo-A and NgR1 were shown to regulate synaptic plasticity, for example, long-term potentiation in the hippocampus and in the sensory-motor cortex, [18][19][20][21][22] whereas the effects of neuronal Nogo-A after injury are not yet well understood. During development, neuronal Nogo-A influences neuronal migration, 23,24 survival, 25,26 cell spreading and neurite growth.…”
mentioning
confidence: 99%